Seroprevalence survey of avian influenza A(H5N1) among live poultry market workers in northern Viet Nam, 2011 - Tham Chi Dung; Pham Ngoc Dinh; Vu Sinh Nam; Luong Minh Tan; Nguyen Le Khanh Hang; Le Thi Thanh; Le Quynh Mai (World Health Organization Regional Office for the Western Pacific, 2014)
Objective: Highly pathogenic avian influenza A(H5N1) is endemic in poultry in Viet Nam. The country has experienced the third highest number of human infections with influenza A(H5N1) in the world. A study in Hanoi in 2001, before the epizootic that was identified in 2003, found influenza A(H5N1) specific antibodies in 4% of poultry market workers (PMWs). We conducted a seroprevalence survey to determine the seroprevalence of antibodies to influenza A(H5N1) among PMWs in Hanoi, Thaibinh and Thanhhoa provinces. Methods: We selected PMWs from five markets, interviewed them and collected blood samples. These were then tested using a horse haemagglutination inhibition assay and a microneutralization assay with all three clades of influenza A(H5N1) viruses that have circulated in Viet Nam since 2004. Results: The overall seroprevalence was 6.1% (95% confidence interval: 4.6-8.3). The highest proportion (7.2%) was found in PMWs in Hanoi, and the majority of seropositive subjects (70.3%) were slaughterers or sellers of poultry. Discussion: The continued circulation and evolution of influenza A(H5N1) requires comprehensive surveillance of both human and animal sites throughout the country with follow-up studies on PMWs to estimate the risk of avian-human transmission of influenza A(H5N1) in Viet Nam.